Development of Unconventional Reservoirs - Rezaee, Reza (MDPI, 2020)
The need for energy is increasing, and at the same time production from conventional reservoirs is declining quickly. This requires an economically and technically feasible source of energy for the coming years. Among some alternative future energy solutions, the most approachable source is from unconventional reservoirs. As the name “unconventional” implies, it requires a different and challenging approach to characterize and develop such a resource. This Special Issue will attempt to cover the most pressing technical challenges for developing unconventional energy sources from shale gas, shale oil, tight gas sand, coalbed methane, and gas hydrates.